Avaliação da toxicidade e correlação com polimorfismos no gene de reparo X-RCC1 em pacientes com neoplasias do trato gastrointestinal submetidos a radio e quimioterapia - SOUZA, Paulo Gustavo Cavalcanti de (Universidade Federal do Pará, 2017)
The intestine tract neoplasms consist in an important problem of Brazil’s health as consequence of its incidence and mortality. Radiotherapy plays a fundamental work as part of gastric and rectal cancer treatment. The vastly background in radiobiology and the recently advances in the comprehension of molecular mechanisms involved in the behaviour of tumour cells and the normal tissues to ionizing radiation has been demonstrating the importance of repair DNA genes. The gene XRCC-1 plays an important work repairing ionizing lesions, working in the answers of single strand break through repairing by base excision. XRCC-1 base polymorphisms can influence the answer of radiotherapy’s answer, in the same way the toxicity showed on them. In the present study we analysed the toxicity of gastric and rectal cancer patients submitted to radiation treatment and chemotherapy and its relation with the occurrence of specifics polymorphisms of XRCC-1 GENE, C194T (rs1799782) and INDEL 4 bp GGCC (rs3213239). Our data showed a general toxicity rate of 64,5 %, but only 24,5 % were grade 3 or 4. The specific toxicity grade 3 or 4 rate were 16,3 % diarrhea, 6 % dermatitis and 6 % nausea. We did not find and correlation between the polymorphisms C194T (rs1799782) and INDEL (rs1799782) and the rate of toxicity found, except when we evaluated patients with gastric and rectal cancer separately. In the latter group, the allele T of C194T was associated with a higher incidence of nausea, with a 10,5 fold risk and a p value of 0,03. Although this positive correlation, we believe that the number of patients in our study was insufficient to a more accurate correlation between toxicity and polymorphisms.